Method of hierarchical cross-layer routing in 802.16 mesh networks. Clustering algorithm - Yevsieieva, O. Yu.; Al-Azzawi Essa Mohammed (ХНУРЕ, 2015)
In TDMA-based IEEE 802.16 mesh wireless networks problem of link resource allocation is turned into problem of time slot assignment which in order to improve network efficiency should be solved jointly with routing as integral cross-layer routing task. In order to increase network scalability a concept of hierarchical cross-layer routing is offered. Main idea is related to clustering and two-level hierarchical control. Lower level is associated with traffic routing and slot allocation within single clusters, where own pool of slots is available and slots’ reusing is prohibited. But upper level controls sizes of the slots’ pools and their allocation among different clusters. Upper control level assumes availability of clusters with same pool of slots thereby saves link resources. And lower and upper control levels are supposed as optimization procedures based on dynamic model in space of states. The offered hierarchical cross-layer routing method includes four components, namely clustering algorithm, algorithm for allocation of pools of slots between different clusters, low and upper level control algorithms. The article is focused on algorithms for clustering and pool allocation. As it was shown every WMN has own optimal cluster’ size which depends on size of WMN and its structure, number of available slots per frame, and incoming traffic intensity. In turn problem of allocation of slots’ pools can be formulated as graph coloring task and can be solved by appropriate algorithms.
Keywords: hierarchical cross-layer routing